Perspektif Islam Tentang Hutang Luar negeri dan Hutang Luar Negeri Negara-Negara Islam - Anto, MB Hendra (Unisia, 2016)
Foreign debt, for quite long time has been considered as one of financial sources for the process of development in various developing countries, including Islamic countries. Some of Islamic countries stand on big outstanding debts that significantly burden them, whereas other countries, conversely, possess huge financial sources. This article tries to analyze the foreign debt from the Islamic perspective, also tries to look at the factual data on the foreign debt among Islamic countries. The article also suggests the solutions needed to overcome the problem pertaining with foreign debt. There is a complex combination between internal arid external factors beyond this problem. The improvement of the economic performance of the country and also the collaboration among Islamic countries are the basic element to solve the problem.